A Semiotic Study of Discourses and Urban Practices in Catholic Sacred and Liminal Spaces: The Case of Saint Anthony’s Feast - Jenny Ponzo; Francesco Galofaro (Religions, 2025)
Descola describes western culture, influenced by the Christian worldview, as “naturalist”. However, semiotic and ethnographic research shows that different perspectives about the relationship between humans and animals coexist with mainstream naturalism. In particular, the introduction of animals in churches is not rare in Italy today, even though it fuels an ongoing debate. The relationship with animals is central in Saint Anthony’s figure and feast, which includes the blessing of animals. This article first focuses on the figure of Saint Anthony, finding in its first sources the seeds of a worldview based on love for creation that fully flourishes centuries later with Saint Francis, then it contextualizes the blessing of animals in the context of a changing sensitivity towards animals, which are often considered from an affective perspective and as part of an ecological standpoint that is also expressed in the institutional discourse of the Catholic Church. Then, the patronal feast of Saint Anthony and the blessing of animals in two different urban communities of Turin (Italy) are the subject of an ethnosemiotic analysis highlighting the animals’ position (inside or at the border of the sacred space), the rite’s structure and the relation between the verbal discourse and the performance of celebrants and worshipers. The position of the animals is thus considered as the expression plane of semantic values about their status in relation to the family.